Ultrasound Alters Pigmentation in Aqueous Solution - Putt, Kelley (My University, 2014)
The use of ultrasound technology has been gaining popularity in many industries as a relatively inexpensive, simple and energy saving technique. Ultrasound induced cavitation through the generation, growth, and collapse of large bubbles liberates high energy. When water is exposed to this high energy, the cavitation phenomenon generates highly reactive hydroxyl and hydrogen ion species. This study investigated the efficacy of ultrasound technology in reducing pigment of annatto, ?-carotene, and anthocyanin in aqueous solution. The cavitation phenomenon and resulting generation of reactive water species was hypothesized to alter the chemical structure of the pigment molecule, thus reducing pigment intensity of annatto, ?-carotene, and anthocyanin in aqueous solution.